Digital Finance Adoption, Emerging Trends, and Customer Satisfaction: A Bibliometric Analysis (Journal of Innovation in Academia, 2025)
The rapid advancement of digital finance has transformed global financial systems, making it critical to understand emerging research trends and customer satisfaction. This study employs a bibliometric analysis using data from the Dimensions database to examine the research trend, collaborative patterns, and thematic focuses in digital finance adoption. The analysis reveals a steady growth in publications over the past decade, with key themes including trust, security, convenience, and service quality. Highly cited sources include top-ranked journals such as the International Journal of Information Management, emphasizing the academic interest in user-centric digital finance research. The co-authorship analysis shows that research in this field is largely collaborative, with an average of 2.56 authors per document. However, international collaboration is limited (7.45%). The findings offer useful information about enhancing customer-centric strategies and emphasize the necessity of collaboration, as well as a focus on data security, privacy, and regulation in future research.